1981
DOI: 10.1111/j.1748-1716.1981.tb06752.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of antidromic and substance P‐induced vasodilatation by a substance P antagonist

Abstract: Indirect evidence has abundantly been presented to support the view that substance P (SP) is involved in the vasodilatation following activation of fine calibre pain fibres (Lembeck & Holzer 1979). In this respect, the dental pulp is interesting since it is richly supplied with SP‐immunoreactive nerves originating from the trigeminal system (Olgart et al. 1917b, Brodin et al. 1980). These nerves are in all probability related to nociception (Henry et al. 1980). Recent observations in the cat showing that elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Baccaglini-and Hogan in the rat saphenous nerve release one or more compounds that can produce local inflammatory changes in the surrounding tissue (42). Substance P is currently considered the most likely mediator of this neurogenic inflammation (43)(44)(45). However, it remains possible that some unmyelinated pain fibers contain and release other peptides, either alone or together with substance P.…”
Section: Neuronsmentioning
confidence: 99%
“…Baccaglini-and Hogan in the rat saphenous nerve release one or more compounds that can produce local inflammatory changes in the surrounding tissue (42). Substance P is currently considered the most likely mediator of this neurogenic inflammation (43)(44)(45). However, it remains possible that some unmyelinated pain fibers contain and release other peptides, either alone or together with substance P.…”
Section: Neuronsmentioning
confidence: 99%
“…Antidromic trigeminal nerve stimulation has been shown to cause SP release from nerve terminals in the dental pulp (8,9) and eye (10). Furthermore, it has been shown that the antidromic vasodilation in the pulp (11) and the inflammation in the eye on IR irradiation (12) can be inhibited by SP antagonists. Recent studies suggest that capsaicin-sensitive sensory nerves of vagal origin can induce neurogenic inflammation and bronchoconstriction in the respiratory tract (13,14).…”
mentioning
confidence: 99%
“…In earlier both in vivo (Maggie et al, 1985(Maggie et al, , 1986) and in vitro (Erspamer et al, 1981;Sj6gren et al, 1982) studies similar excitatory motor effects of SP were demonstrated. The motor response of the bladder to SP observed in this study is suggested to be specific for the peptide, since the SP-analogue (D-Pro 2, D-Trp 7' 9)-SP, known to block SP-receptors Leander et al, 1981;Rosell et al, 1981), almost completely inhibited contraction. Furthermore, the bladder contraction induced by electrical stimulation of the preganglionic pelvic nerves was significantly reduced by high doses of the SP-analogue infused regionally via the superior vesical artery.…”
Section: Discussionmentioning
confidence: 82%